2015
DOI: 10.1155/2015/516843
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Treatment Results of High-Grade Osteosarcoma in Norway: A Scope Beyond the “Classical” Patient

Abstract: Purpose. A retrospective study of prognostic factors and treatment outcome of osteosarcoma (OS) during modern chemotherapy era with focus on patients with primary metastatic disease, nonextremity localisation, or age >40 years (nonclassical OS). Methods. A nationwide cohort, comprising 424 high-grade Norwegian bone OS patients, was based on registry sources supplemented with clinical records from hospitals involved in sarcoma management between 1975 and 2009. Results. Only 48% were younger patients with tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 76 publications
7
34
1
Order By: Relevance
“…Tumor location and resectability, metastatic disease at diagnosis, response to chemotherapy and local recurrence are known prognostic factors for osteosarcoma and Ewing sarcoma according to published reports 8,26,[28][29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor location and resectability, metastatic disease at diagnosis, response to chemotherapy and local recurrence are known prognostic factors for osteosarcoma and Ewing sarcoma according to published reports 8,26,[28][29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Adequate surgery implied surgical removal of the primary tumor with wide or marginal margins as described by Enneking et al (13), while adequate chemotherapy was defined as having received at least six courses of chemotherapy. The latter definition with its justification, is more thoroughly presented in a previous study (5). Patients with metastatic disease at the time of diagnosis were in need for a surgical remission for both primary tumor and metastases in order to be classified as having undergone adequate surgical treatment.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that axial tumor locations of osteosarcoma (OS) result in a worse outcome than primary disease located in the appendicular skeleton (1)(2)(3)(4)(5). Proximal osteosarcoma in extremity long bones (POS) has also been associated with poor outcome (4,(6)(7)(8), although the prognostic impact of the anatomical location of such tumors is still debated (6,8,9).…”
Section: Abstract Background/aim: This Study Aimed To Identify the Pmentioning
confidence: 99%
“…), the prognosis for confirmed cases is depressing, especially for those in advanced stage (Pediatric Treatment Editorial Board ; Berner et al . ). Several prognostic factors comprised of primary tumour site (Goldstein‐Jackson et al .…”
Section: Introductionmentioning
confidence: 97%
“…Contrary to the young population, osteosarcoma occurs in the aged patients more commonly in axial skeletons rather than long tubular bones, especially in areas that have been previously irradiated or have bone abnormalities (Hayden & Hoang 2006). Although the prevalence rate is relatively low when compared with other tumour types (Ottaviani & Jaffe 2009;Hung et al 2014), the prognosis for confirmed cases is depressing, especially for those in advanced stage (Pediatric Treatment Editorial Board 2002;Berner et al 2015). Several prognostic factors comprised of primary tumour site (Goldstein-Jackson et al 2005), tumour size (Pakos et al 2009), and clinically detectable metastasis (Pediatric Treatment Editorial Board 2002) have been identified to be significantly associated with the 5-year survival rate.…”
Section: Introductionmentioning
confidence: 99%